PENGARUH MEDIA PEMBELAJARAN EKONOMI BERBASIS APLIKASI QUIZIZZ TERHADAP PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR - Firmansan Sanjaya; Yudho Ramafrizal; Saiful Almujab (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine: (i) a description of quizizz application-based economic learning media (ii) a description of students' learning motivation (iii) a description of student learning achievement (iv) the effect of quizizz application-based economic learning media on increasing learning motivation (v) the effect quizizz application-based economic learning media to increase learning achievement in economics subjects class XI IPS SMAN 9 Bandung. The results showed that: (i) students agreed with the use of quizizz application-based learning media with an average percentage of 3.56, students' learning motivation was considered good with an average of 3.76, student learning achievement was included in the category good with an average of 84.91 (ii) there is an effect of 61.3% between quizizz application-based learning media on students' learning motivation with statistical analysis t count > t table (10.131 > 2.007) (iii) there is an effect of 53 .6% between quizizz on student achievement with statistical analysis t count > t table (8.671 > 2.004).